The glucose-responsive transcription factor ChREBP contributes to glucose-dependent anabolic synthesis and cell proliferation - Tong, Xuemei (National Academy of Sciences, 2009)
Tumor cells are metabolically reprogrammed to fuel cell proliferation. Most transformed cells take up high levels of glucose and produce ATP through aerobic glycolysis. In cells exhibiting aerobic glycolysis, a significant fraction of glucose carbon is also directed into de novo lipogenesis and nucleotide biosynthesis. The glucose-responsive transcription factor carbohydrate responsive element binding protein (ChREBP) was previously shown to be important for redirecting glucose metabolism in support of lipogenesis in nonproliferating hepatocytes. However, whether it plays a more generalized role in reprogramming metabolism during cell proliferation has not been examined. Here, we demonstrated that the expression of ChREBP can be induced in response to mitogenic stimulation and that the induction of ChREBP is required for efficient cell proliferation. Suppression of ChREBP resulted in diminished aerobic glycolysis, de novo lipogenesis, and nucleotide biosynthesis, but stimulated mitochondrial respiration, suggesting a metabolic switch from aerobic glycolysis to oxidative phosphorylation. Cells in which ChREBP was suppressed by RNAi exhibited p53 activation and cell cycle arrest. In vivo, suppression of ChREBP led to a p53-dependent reduction in tumor growth. These results demonstrate that ChREBP plays a key role both in redirecting glucose metabolism to anabolic pathways and suppressing p53 activity.